(untitled) - Serway, Raymond A. (Philadelphia, 1987)
The country's bestselling calculus-based physics text, recognized by over 700 schools for its currency, accuracy, and clarity, has received a carefully crafted revision. Its strong problem solving approach, incorporating new intermediate and challenging problems, innovative spreadsheet problems, and ground-breaking conceptual problems with reasoning statements teach students how to think through physical examples as opposed to plugging numbers into formulas. Complementing this unsurpassed textbook is an exceptional ancillary package, complete with interactive multimedia support. Features: * The Laws of Motion are discussed thoroughly in chapter 5 and serve as building blocks for the remainder of the course material. * Conceptual Examples with detailed reasoning statements help students build on cumulative knowledge of concepts and learn how to think through physical situations rather than simply plugging in numbers to formulas. * Additional beneficial pedagogy includes chapter previews, marginal notes, vivid illustrations, biographical sketches, problem-solving strategies, summaries, thought questions, conceptual problems, spreadsheet problems, and summaries. * Paired problems at the end of each chapter test the students' ability to understand the concept being asked of them and their ability to set up the initial equation, as well as testing their mathematical manipulation of the same problem. New to this edition: * A line-by-line edit has improved the currency, accuracy, and clarity that earned the text its superb reputation. * New spreadsheet problems appear at the end of most chapters, enhancing students' ability to use the tool and gain more practical knowledge of subject matter. A disk containing templates will be available to all students using the text. * Many new intermediate level problems appear at the end of each chapter and offer students more practical exercises covering chapter concepts. * New challenging problems at the end of each chapter, colour-coded for quick recognition, demand and inspire mastery of content. * Interactive Physics II(TM) software brings textbook simulations to life, keying specific figures and examples from the text, as well as representing material difficult to present in textbook format. This state-of-the-art program offers students greater understanding in an engaging format * SD2000, a self-contained software package of physics simulations and demonstrations, has been customized to accompany Serway's text. Its capabilities span mechanics, waves, thermodynamics, E & M, optics, and some modern physics topics. Keyed to SD2000 Boxes in text.
Keywords: Physics,Vật lý